Insurance of the Termination Risk of Projects with Joint Companion Activity - Sukhorukova, Irina; Chistyakova, Natal’ya (Journal of Reviews on Global Economics, 2018)
Actuarial calculations are based on the study of mathematical models of financial schemes in insurance taking into account the stochastic nature of insurable events. They lie at the intersection of mathematical and economic disciplines. This paper is devoted to the formulation and investigation of the mathematical model of insurance of a joint project of partners from the risk of its early termination due to the retirement of one of the companions due to external circumstances. In case of an insured event, the partner remaining in the project receives insurance to continue the project. In order to assess the obligations of the insurance company, an economic-mathematical model of personal joint insurance of participants has been constructed to calculate the necessary characteristics of such an agreement. To describe the dynamically changing threats to terminate the insurance contract, the concepts of the intensity of retirement functions of insured persons are introduced, which are convenient in the study of insurance contracts with several participants. Possibilities of payment of insurance compensation to each partner are received and probability of that the insurance company should pay insurance compensation are received. Calculations are made using the example of specific functions of the intensity of retirement of partners. Practical recommendations are given related to the use of numerical methods or simulation methods in calculations based on the obtained universal formulas.